THE INFLUENCE OF USE OF TEACHING MEDIA ON STUDENTS LEARNING OUTCOMES TO PROMOTE THEIR POSITIVE LEARNING BEHAVIOUR - Eka Ristianingsih; Djunaidi Djunaidi (Esteem Journal of English Education Study Programme, 2023)
The aim of this study was to examine the impact of utilizing cliff board media on student learning outcomes in a first-grade class at SDN Rawadadi. The research method employed was experimental research, specifically utilizing a Pre-Experimental Design known as the One Group Pretest-Posttest Design. The population for this study consisted of 20 first-grade students at SDN Rawadadi, and the entire population was selected as the sample. The results of the calculations indicated a T-count value of 5.748, which is greater than the T-table value of 1.734 in the T-test sample. Furthermore, the sig. (2-tailed) value was 0.000, which is less than 0.05, meeting the prerequisites for hypothesis testing. Therefore, the hypothesis was accepted. Based on the hypothesis testing data, it can be concluded that the utilization of cliff board media has a significant impact on student learning outcomes.